Futsal training, technique and tactics - Sturgess, Peter (Bloomsbury Sport, 2017)
Many of the top world-class professional football players played Futsal in their youth (Pele, Luis Figo, Lionel Messi, Cristiano Ronaldo, Xavi and Fabregas) and have stated that playing the game made them the great players they are today. Futsal is an exciting, fast moving game of technique, skill, tactics and physical endeavour. Players take the ultimate challenge by testing their skills under the most intense pressure due to the lack of time and space. Coaches face huge tactical challenges as the game changes minute by minute. It is for these reasons that Futsal has taken a huge grip upon the football landscape and the development of players from grassroots upwards. This book is the ideal book to assist players and coaches in honing their futsal skills and techniques. If you want to be the new Messi, Ronaldo or Fabregas, can you afford not to read this book?